De impossibilidades e limites da representação em três textos de Marguerite Duras - Berned, Pablo Lemos (2009)
This work aims at verify the implications in Marguerite Duras literary aesthetic by proposing the denial of representation, through transgression to the traditional narrative. Starting from three texts by Duras which dialogue with the cinematographic language Le camion (1977), Le Navire Night (1979) and La maladie de la mort (1983), this work, throughout three chapters, recognizes in these novels denounce writing, in which the language itself unveils and unmasks its mechanisms. The first chapter proposes the discussion about the different concepts of representation and the search of Duras writing for a possible beyond the truth of what the words hide. At a second moment, I reflect about the impossibility of Duras writing in express an absolute view about the world to be represented, where the dialogue with other languages is an attempt to overcome the condition of discontinuity appropriate to the existence. Finally, in the last chapter, the possible meanings in an aesthetic answer aiming at denying the representation is sought: Duras writing is recongnized as transgression and a refusal of the definitive. The demystifying sincerity to which Duras writing proposes to do, faces the collapse of rationality, with only the experience and limits of dissolution and certainty being left.